2019
DOI: 10.4054/mpidr-wp-2019-017
|View full text |Cite
|
Sign up to set email alerts
|

The gendered impacts of delayed parenthood on educational and labor market outcomes: a dynamic analysis of population-level effects over young adulthood

Abstract: Later parenthood is often beneficial for women, but less is known about its impact on men. As first births continue to occur later in life, it is important to understand whether this delay influences the educational and labor market outcomes of women and men differently, and how it changes the socioeconomic characteristics of children's parents at birth. However, education, employment, and fertility are linked, implying that complex models are required in order to analyze the time-varying impacts of delayed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 102 publications
(156 reference statements)
1
4
0
Order By: Relevance
“…First, we found that a delay in the entry of motherhood leads to higher educational attainment of women. This finding echoes previous studies showing that education partially mediates the effect of fertility timing on women's more favourable labour market outcomes, although these studies have focused more strongly on younger ages (Blackburn et al, 1993;Buckles, 2008;Chandler et al, 1994;Nisén et al, 2019). However, the mediation analysis suggests that higher education contributes little to our understanding of the effect of fertility timing on earnings of women in midlife.…”
Section: Main Findings and Implicationssupporting
confidence: 78%
See 4 more Smart Citations
“…First, we found that a delay in the entry of motherhood leads to higher educational attainment of women. This finding echoes previous studies showing that education partially mediates the effect of fertility timing on women's more favourable labour market outcomes, although these studies have focused more strongly on younger ages (Blackburn et al, 1993;Buckles, 2008;Chandler et al, 1994;Nisén et al, 2019). However, the mediation analysis suggests that higher education contributes little to our understanding of the effect of fertility timing on earnings of women in midlife.…”
Section: Main Findings and Implicationssupporting
confidence: 78%
“…Moreover, only few studies so far studied the mediating effect of total number of children (Amuedo-Dorantes & Kimmel, 2005;Buckles, 2008;Herr, 2016;Karimi, 2014), given common sample restrictions to earlier ages. Lastly, this study contributes to the discrepant evidence on the labour market effects of fertility timing in Europe (Bratti & Cavalli, 2014;Cantalini et al, 2017;Fitzenberger et al, 2013;Frühwirth-Schnatter et al, 2016;Karimi, 2014;Kind & Kleibrink, 2012;Leung et al, 2016;Lundborg et al, 2017;Nisén et al, 2019;Picchio et al, 2021;Putz & Engelhardt, 2014;Rosenbaum, 2021). This study is situated in the country context of the United Kingdom (UK), where public support for working mothers is weak as compared to other European countries (Brooks, 2012;Sigle-Rushton, 2008), leading to the expectation that motherhood timing may be consequential for mothers' earnings more similar to the US, and potentially also in the long term.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations